2020
DOI: 10.3390/plants9121801
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Symbiotic Microorganisms, Nutrient Uptake and Rhizosphere Bacterial Community in Response of Pea (Pisum sativum L.) Genotypes to Elevated Al Concentrations in Soil

Abstract: Aluminium being one of the most abundant elements is very toxic for plants causing inhibition of nutrient uptake and productivity. The aim of this study was to evaluate the potential of microbial consortium consisting of arbuscular mycorrhizal fungus (AMF), rhizobia and PGPR for counteracting negative effects of Al toxicity on four pea genotypes differing in Al tolerance. Pea plants were grown in acid soil supplemented with AlCl3 (pHKCl = 4.5) or neutralized with CaCO3 (pHKCl = 6.2). Inoculation increased shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 90 publications
(156 reference statements)
1
7
0
Order By: Relevance
“…Concentrations of sodium, potassium and phosphorus in the roots and the 1st and 2nd mature leaves of wheat plants were assessed as previously described [ 30 ] using an ICPE-9000 inductively coupled plasma emission spectrometer (Shimadzu, Kyoto, Japan). For this purpose, plant samples were digested in a mixture of concentrated HNO 3 and 38% H 2 O 2 at 70 °C using a DigiBlock digester (LabTech, Sorisole, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of sodium, potassium and phosphorus in the roots and the 1st and 2nd mature leaves of wheat plants were assessed as previously described [ 30 ] using an ICPE-9000 inductively coupled plasma emission spectrometer (Shimadzu, Kyoto, Japan). For this purpose, plant samples were digested in a mixture of concentrated HNO 3 and 38% H 2 O 2 at 70 °C using a DigiBlock digester (LabTech, Sorisole, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Studies with individual microbial taxa have demonstrated that these can promote growth and stress tolerance of plants (Lugtenberg and Kamilova, 2009) and influence pathogen and herbivore resistance (Pieterse et al, 2014;Hu et al, 2018). More recent studies with complex microbiomes have confirmed these effects: inoculation with diverse microbiota altered plant growth and physiology (Fitzpatrick et al, 2019;Belimov et al, 2020), phenology (Panke-Buisse et al, 2015), and pathogen resistance (Berendsen et al, 2018;Berg and Koskella, 2018), sometimes in a genotype-or environment-dependent fashion (Berg and Koskella, 2018;Belimov et al, 2020).…”
Section: Two Perspectives In Plant Microbiome Researchmentioning
confidence: 97%
“…Concentrations of sodium, potassium and phosphorus in the roots and first and second mature leaves of wheat plants were assessed using an ICPE-9000 inductively coupled plasma emission spectrometer (Shimadzu, Kyoto, Japan) [ 31 ]. For this purpose, plant samples were digested in a mixture of concentrated HNO 3 and 38% H 2 O 2 at 70 °C using a DigiBlock digester (LabTech, Sorisole, Italy).…”
Section: Methodsmentioning
confidence: 99%